Book Reviews. Issue 1 (1st March 2019) - Zaharijević, Adriana; Ghodsee, Kristen; Kanner, Efi; von Klimó, Árpád; Stibbe, Matthew; Zhurzhenko, Tatiana; Svirčev, Žarka; Ignaciuk, Agata; Kuhnle, Sophia; Miškovska Kajevska, Ana; Bonfiglioli, Chiara; Hughson, Marina; et al.
Abstract : Athena Athanasiou, Agonistic Mourning: Political Dissidence and the Women in Black, Edinburgh: Edinburgh University Press, 2017, xii + 348 pp., £19.99 (paperback), ISBN 978-1-4744-2015-0. Maria Bucur and Mihaela Miroiu, Birth of Democratic Citizenship: Women and Power in Modern Romania, Bloomington: University of Indiana Press, 2018, 189 pp., 35.00 (рaperback), ISBN 978-0-25302-564-7. Katherina Dalakoura and Sidiroula Ziogou-Karastergiou, Hē ekpaideusē tôn gynaikôn, gynaikes stēn ekpaideusē: Koinônikoi, ideologikoi, ekpaideutikoi metaschēmatismoi kai gynaikeia paremvasē (18os–20os ai.) (Women's education, women in education: Social, ideological, educational transformations, and women's interventions [18th–20th centuries]), Athens: Greek Academic Electronic Manuals/Kallipos Repository, 2015, 346 pp., e-book: http://hdl.handle.net/11419/2585, ISBN: 978-960-603-290-5. Provided free of charge by the Association of Greek Academic Libraries. Melissa Feinberg, Curtain of Lies: The Battle over Truth in Stalinist Eastern Europe, New York: Oxford University Press, 2017, 232 pp., 74.00 (hardback), ISBN 978-0-19-064461-1. Christa Hämmerle, Oswald Überegger, and Birgitta Bader Zaar, eds., Gender and the First World War, Basingstoke, UK: Palgrave Macmillan, 2014, 276 pp., £69.99 (paperback), ISBN 978-1-349-45379-5. Oksana Kis, Ukrayinky v Hulahu: Vyzhyty znachyt' peremohty (Ukrainian women in the Gulag: Survival means victory), Lvіv: Institute of Ethnology, 2017, 288 pp., price not listed (paperback), ISBN: 978-966-02-8268-1. Ana Kolarić, Rod, modernost i emancipacĳ a: Uredničke politike u časopisima "Žena" (1911–1914) i "The Freewoman" (1911–1912) (Gender, modernity, and emancipation: Editorial politics in the journals "Žena" [The woman] [1911–1914] and "The Freewoman" [1911–1912]), Belgrade: Fabrika knjiga, 2017, 253 pp., €14 (paperback), ISBN 978-86-7718-168-0. Agnieszka Kościańska, Zobaczyć łosia: Historia polskiej edukacji seksualnej od pierwszej lekcji do internetu (To see a moose: The history of Polish sex education from the first lesson to the internet), Wołowiec: Czarne, 2017, 424 pp., PLN 44.90 (hardback), ISBN 978-83-8049-545-6. Irina Livezeanu and Árpád von Klimó, eds., The Routledge History of East Central Europe since 1700, New York: Routledge, 2017, 522 pp., GBP 175 (hardback), ISBN 978-0-415-58433-3. Zsófia Lóránd, The Feminist Challenge to the Socialist State in Yugoslavia, Basingstoke, UK: Palgrave Macmillan 2018, 270 pp., €88.39 (hardback), €71.39 (e-book), ISBN 978-3-319-78222-5. Marina Matešić and Svetlana Slapšak, Rod i Balkan (Gender and the Balkans), Zagreb: Durieux, 2017, 333 pp., KN 168 (hardback), ISBN 978-953-188-425-9. Ana Miškovska Kajevska, Feminist Activism at War: Belgrade and Zagreb Feminists in the 1990s, London: Routledge, 2017, 186 pp., £105.00 (hardback), ISBN 978-1-138-69768-3. Ivana Pantelić, Uspon i pad "prve drugarice" Jugoslavĳ e: Jovanka broz i srpska javnost, 1952–2013 (The rise and fall of the "first lady comrade" of Yugoslavia: Jovanka Broz and Serbian public, 1952–2013), Belgrade: Službeni glasnik, 2018, 336 pp., RSD 880 (paperback), ISBN 978-86-519-2251-3. Fatbardha Mulleti Saraçi, Kalvari i grave në burgjet e komunizmit (The cavalry of women in communist prisons), Tirana: Instituti i Studimit të Krimeve dhe Pasojave të Komunizmit; Tiranë: Kristalina-KH, 2017, 594 pp., 12000 AL Lek (paperback), ISBN 978-9928-168-71-9. Žarka Svirčev, Avangardistkinje: Ogledi o srpskoj (ženskoj) avangardnoj književnosti (Women of the avant-garde: Essays on Serbian (female) avant-garde literature), Belgrade, Šabac: Institut za književnost i umetnost, Fondacĳ a "Stanislava Vinaver, " 2018, 306 pp., RSD 800 (paperback), ISBN 978-86-7095259-1. Şirin Tekeli, Feminizmi düşünmek (Thinking feminism), İstanbul: Bilgi University, 2017, 503 pp., including bibliography, appendices, and index, TRY 30 (paperback), ISBN: 978-605-399-473-2. Zafer Toprak, Türkiye'de yeni hayat: Inkılap ve travma 1908–1928 (New life in Turkey: Revolution and trauma 1908–1928), Istanbul: Doğan Kitap, 2017, 472 pp., TRY 40 (paperback), ISBN 978-605-09-4721-2. Wang Zheng, Finding Women in the State: A Socialist Feminist Revolution in the People's Republic of China, 1949–1964, Berkeley: University of California Press, 2016, 380 pp., 31.45 USD (paperback), ISBN 978-0-520-29229-1.